Low vancomycin trough concentration in neonates and young infants. Issue 5 (24th March 2021) - Maruyama, Hidehiko; Tanzawa, Ayano; Funaki, Takanori; Ito, Yushi; Isayama, Tetsuya
Abstract: Background: Vancomycin (VCM) is useful for treating methicillin‐resistant Staphylococcus aureus . In infants, calibrating the initial VCM dose is difficult, and many regimens have been proposed. For instance, our center uses the VCM regimen recommended for infants in the 2012–13 Nelson's Pediatric Antimicrobial Therapy . Nonetheless, our experience has shown that the initial VCM trough concentrations were frequently off target. We therefore analyzed the data on the initial VCM trough concentration in infant patients at our center. Methods: The study subjects were inborn infants born between July 2014 and June 2019 who were given VCM at earlier than day 60 in the neonatal intensive care unit. The primary outcome was the initial VCM trough concentration. The patients were divided into three groups by VCM trough concentration: <10, 10–15, and >15 mg/L. We also estimated VCM trough concentration by one method using Monte Carlo simulation, based on Nelson regimen dosage. Results: Thirty‐three patients were analyzed. The number of patients with <10, 10–15, and >15 mg/L was 24, 4, and 5, respectively. There was no significant difference in clinical characteristics between <10 versus 10–15 and 10–15 versus >15 mg/L. The numbers of patients with <10, 10–15, and >15 mg/L in the simulation were 26, 6, and 1, respectively. Conclusions: Most initial VCM trough concentrations were below the target. We could not find any significant clinical characteristics, which affected VCM trough concentration. Increasing the VCM dosage of the Nelson regimen with simulation should therefore be considered.